Pemikiran Ibn Taymīyah tentang Sharī‘ah sebagai Tujuan Tasawuf - Izzuddin Washil; Ahmad Khoirul Fata (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
Ibn Taymīyah rejects no all doctrines of Sufism, although he criticizes some of them. For instance, he does firmly refuse the doctrine of waḥdat al-wujūd and fanā’ altogether. Ibn Taymīyah has a unique concept of Sufism, which differs from other concepts of Sufism promulgated by other Sufis, especially those of Wujūdīyah proponents. Ibn Taymīyah’s concept of Sufism puts great emphasis on its appropriateness with stipulations of sharī‘ah. The compatibility of sharī‘ah and taṣawwuf has been the main feature of his model of Sufism. When other Sufis start their mystical journey from the stage of sharī‘ah, Ibn Taymīyah puts sharī‘ah as the final stage. To him, sharī‘ah is the main goal of mystical journeys; taṣawwuf should be based on sharī‘ah, and it also must end with sharī‘ah. Using al-Taftazānī’s perspective, this study finds that the character of Ibn Taymīyah’s Sufism is Taṣawwuf Akhlāqī. This is so because he prefers to purify morality than such mystical experiences as waḥdat al-wujūd or fanā’ and the uses of symbols to reveal the mystical experiences.